The effectiveness of moringa leaves extract to prevent stunting at toddlers aged 23-59 months - Budiono, Nugrahadi Dwi Pasca; Has, Dwi Faqihatus Syarifah (Institute of Computer Science (IOCS), 2025)
Background: Stunting remains a critical public health challenge, particularly in low- and middle-income countries, where inadequate nutrition affects child growth and development. One of the main factors causing stunting is chronic malnutrition in early life. Moringa (Moringa oleifera) leaves are rich in essential nutrients, including proteins, vitamins, and minerals, which are vital for growth. This study investigates the effectiveness of Moringa leaves extract in preventing stunting among toddlers aged 23–59 months. Method’s: This study involved 40 participants who were in kebomas sub-district, gresik district. A randomized controlled trial was conducted with an intervention group receiving Moringa leaves extract supplementation and a control group receiving standard nutrition. Anthropometric measurements, including height-for-age Z-scores (HAZ), were recorded at baseline and after a 6-month intervention period. The results indicate a significant improvement in HAZ scores in the intervention group compared to the control group (p < 0.05). Additionally, children who received Moringa supplementation showed better appetite, improved hemoglobin levels, and enhanced overall nutritional status. Conclusion: These findings suggest that Moringa leaves extract can be an effective, affordable, and sustainable strategy for preventing stunting in vulnerable populations. However, further research is needed to determine the optimal dosage and long-term effects. Integrating Moringa supplementation into nutrition programs could be a promising approach to combating childhood stunting and improving global child health outcomes.